EKSISTENSI TANAH WAKAF DALAM PEMANFAATANNYA UNTUK KEMAJUAN KESEJAHTERAAN UMUM - Salmawati Salmawati (JCH (Jurnal Cendekia Hukum), 2019)
The research objective is to find out, analyze The existence of land endowments in its use for the advancement of general welfare. This study uses a normative legal research type (doctrinal) to analyze phenomena or (social) phenomena that occur in society that are related to the legal reality in society, namely various laws and regulations in the land endowments. The results showed that, (the existence of waqf land is perpetuating the benefits of waqf objects in accordance with the purpose of waqf, namely realizing the economic potential and benefits of waqf property for the sake of worship and to promote general welfare.